FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MENARCHE DINI PADA SISWI SEKOLAH MENENGAH PERTAMA (SMP) DI KOTA DENPASAR - Suartiningsih, Ni Putu; Widarini, Ni Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Early menarche can increase the risk of ovarian cancer, breast cancer, and anemia. This study aims to determine the factors associated with the incidence of early menarche in junior high school students in Denpasar City. This research is a quantitative analytic study with a cross sectional study design. The research locations were conducted in two public and private junior high schools respectively. The time of the research starts from January-May 2023. The research sample is class VII students, totaling 287 people. The research sample was taken using a multistage random sampling technique. The variable in this study is early menarche, junk food, physical activity, mass media, socio-economic, age of mother's menarche, and sleep rest. Data was obtained through filling out a structured questionnaire and data analysis used simple logistic regression. The results showed 49.48% experienced early menarche. Variables that were related to the incidence of early menarche were junk food, physical activity, mass media, socioeconomics, and maternal menarche, while the variables that were not related to the incidence of early menarche were sleep rest. Provision of information on a regular basis, especially regarding factors related to menarche, needs to be done early to minimize the occurrence of early menarche. Keywords: Early Menarche, Junk Food, Mass Media, Social Economy, Maternal Menarche